2016
DOI: 10.4238/gmr.15038574
|View full text |Cite
|
Sign up to set email alerts
|

Diallel analysis to choose parents for black bean (Phaseolus vulgaris L.) breeding

Abstract: ABSTRACT. In this study, conducted in two different seasons, we aimed to choose parents to obtain promising segregating populations for the extraction of black bean (Phaseolus vulgaris L.) lines that are superior in terms of disease resistance, plant architecture, and grain yield. Twelve parents were arranged in two groups to compose a partial diallel in a 5 x 7 scheme. Group 1 was composed of parents with black grains and erect plant architecture, while group 2 was composed of parents that had carioca grains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The significant effect of populations by the deviance analysis suggests that the variability among populations, for both characters, originates from the genetic difference between the parents. These results corroborate those of Moura et al (2016), who found a significant difference between the two groups of parents for grain yield and plant architecture in a diallel analysis study. Common bean plants with a desirable architecture are positively correlated with higher HD values.…”
Section: Deviance Analysis and Genetic Parameters Estimationsupporting
confidence: 90%
“…The significant effect of populations by the deviance analysis suggests that the variability among populations, for both characters, originates from the genetic difference between the parents. These results corroborate those of Moura et al (2016), who found a significant difference between the two groups of parents for grain yield and plant architecture in a diallel analysis study. Common bean plants with a desirable architecture are positively correlated with higher HD values.…”
Section: Deviance Analysis and Genetic Parameters Estimationsupporting
confidence: 90%
“…This fact is relevant because the higher the coefficient of kinship between populations, the more difficult it is to discriminate them. For traits controlled by fewer genes, such as disease resistance, plant architecture, and grain appearance (Batista et al, 2017;Moura et al, 2016;Silva et al, 2013), lower variability between populations is expected because they share the same alleles from the common parent. Thus, all the variability between populations is conditioned to the noncommon parent.…”
Section: Discussion Genetic Effects Of the Modelmentioning
confidence: 99%
“…Therefore, the higher the F ST is, more important the population merit is for a given trait. Higher values of F ST of the populations for plant architecture and grain yield are associated with the genetic divergence among genitors, in which well‐yielded genitors were crossed with upright genitors in order to start a recurrent program for black beans (Moura et al., 2016). Despite the genitors being divergent for grain appearance, genetic variability among populations decreases after early selection for this trait, making the F ST the lowest.…”
Section: Discussionmentioning
confidence: 99%